1987
DOI: 10.1128/iai.55.12.2956-2961.1987
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-lipopolysaccharide-induced release of lactoferrin from human polymorphonuclear leukocytes: role of monocyte-derived tumor necrosis factor alpha

Abstract: We have examined the role played by human peripheral blood monocytes in mediating responses of human polymorphonuclear leukocytes (PMN) to bacterial lipopolysaccharide (LPS) in vitro. When incubated with Salmonella typhimurium LPS at 37°C, human PMN suspended in serum-free buffer released the specific granule constituent lactoferrin into the surrounding medium. Release of lactoferrin from PMN varied with the concentration of LPS (1 to 1,000 ng/ml) as well as with the duration of incubation (2 to 60 min) and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our study confirms that TNF induces the generation of LF (13,16). In addition, TNF had a significant stimulative effect on the generation of TPL in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…Our study confirms that TNF induces the generation of LF (13,16). In addition, TNF had a significant stimulative effect on the generation of TPL in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…Lactoferrin levels in plasma are known to increase during inflammation, accompanied by a decrease in the lactoferrin content of PMN (19,45). Lactoferrin is stored in secondary granules, and several cytokines as well as LPS are able to induce its release (1,25). Further studies are needed to know whether other proteins released by PMN could potentiate and act in concert with lactoferrin in inhibiting Candida growth and whether this activity relies only on the depletion of iron in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Ability of lactoferrin itself to inhibit Candida growth and its importance in the anticandidal activity of neutrophils. Since lactoferrin acts as a bacteriostatic agent (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and, as shown by the results in the preceding sections, it was released in appreciable amounts during LPS stimulation, we examined whether lactoferrin had a direct effect on the growth of C. albicans. By the same rapid [3H]glucose uptake assay used to assay lysis of PMN, we found that this iron-binding protein was able to inhibit C. albicans growth in a dose-dependent manner over a range from 1 to 100 p,g/ml.…”
Section: Effect Of Various Lps On Neutrophil Anti-candida Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that within 15 min after the first administration of 5 mg OKT3, complement activation via the classical pathway occurred, followed by early activation of neutrophils [MI. The late and sustained activation of neutrophils contributed to the release of cytokines [5,13,17,191. As with septic shock, activation of complement and neutrophils has been considered a possible pathogenetic factor in the development of side effects following the first administration of OKT3 [ll, 12,14,20,21,25].…”
Section: Discussionmentioning
confidence: 99%